2020
DOI: 10.1177/1359105320937068
|View full text |Cite
|
Sign up to set email alerts
|

Coping with childhood maltreatment: Avoidance and eating disorder symptoms

Abstract: Childhood maltreatment is associated with eating disorder symptoms; however, the nature of this association is unclear. We found those who experienced childhood maltreatment had higher avoidant coping and eating disorder symptoms. We also found an additive effect for maltreatment, such that with more types of maltreatment experienced, avoidant coping and eating disorder symptoms were greater. We also found evidence of an indirect effect such that childhood maltreatment was related to eating disorder symptoms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Findings underscore that CT in itself does not equal post-traumatic sequelae, but that mediators such as PTSD, emotion dysregulation, and/or interpersonal difficulties may be at play to complicate and prolong the treatment course. This concurs with research suggesting that PTSD, emotional dysregulation, interpersonal difficulties, and avoidant personality styles mediate CT’s impact on ED development, severity, and chronicity [ 2 , 10 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Findings underscore that CT in itself does not equal post-traumatic sequelae, but that mediators such as PTSD, emotion dysregulation, and/or interpersonal difficulties may be at play to complicate and prolong the treatment course. This concurs with research suggesting that PTSD, emotional dysregulation, interpersonal difficulties, and avoidant personality styles mediate CT’s impact on ED development, severity, and chronicity [ 2 , 10 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 87%
“…A network analysis of ED and PTSD bridge symptoms found associations between bingeing and irritability, body dissatisfaction and distressing dreams, and shape difficulties and concentration difficulties [ 11 ]. CT in EDs also associate with avoidant coping and ED symptoms in a dose–response manner [ 12 ], supporting that childhood sexual abuse with avoidant personality predict ED chronicity [ 13 ]. In fact, avoidance, rumination and suppression of emotional expression are all linked to increased ED severity.…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis by Molendjik et al [14] demonstrated that individuals with EDs have experienced CT twice to four times more frequently, and more severely compared to healthy controls. Individuals with EDs who have been exposed to CT were found to experience an early onset and severe pathology of the disease, poor treatment outcomes, as well as high dropout rates [14,[16][17][18][19]. This implies that the treatments available and recommended for individuals with EDs (e.g., [20]) may be less suitable for treating the complex clinical presentations of EDs combined with CT.…”
Section: The Relationship Between Ct and Eds Among Adolescentsmentioning
confidence: 99%
“…Given the increasingly high prevalence rates of overweight and obesity worldwide, 40 and related morbidity and mortality risks, it is crucial to better understand which factors contribute to increased BMI in later adulthood. 41 It has been proposed that alterations in emotional regulation and resulting psychological distress 42 , 43 , 44 , 45 arising from early maltreatment experiences 46 may lead to the development of unhealthy behaviours, such as substance use, poor eating habits, and binge eating, in attempts to cope with life challenges, 47 , 48 thus increasing the risk for overweight and obesity. 45 , 49 Yet, only a few studies have focused on whether psychological distress mediates the relation between childhood maltreatment and BMI in adulthood.…”
mentioning
confidence: 99%